Answer:
g(x) =
![12.((3)/(4))^x](https://img.qammunity.org/2021/formulas/mathematics/high-school/x4vanzrdjfiwe02sfif21fet3g4wla0jeb.png)
Explanation:
Exponential function g has been represented by the table attached,
Equation of the exponential function is,
g(x) =
![a.(b)^x](https://img.qammunity.org/2021/formulas/mathematics/high-school/ldtxgibxtpp2cd8fzreqefdt29uhpxovbk.png)
Now we substitute the values of x and g(x) from the table,
For a point (0, 12),
12 =
![a(b)^0](https://img.qammunity.org/2021/formulas/mathematics/high-school/9tvifof85y3u8j9oqdde8qthak2f6klpho.png)
a = 12
For another point (1, 9),
9 =
![a.(b)^1](https://img.qammunity.org/2021/formulas/mathematics/high-school/1z3obkl7rwpjfquvirv1mmxu3eok1lgggy.png)
9 = a × b
9 = 12 × b
b =
![(9)/(12)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/en3bdlz42vd1so3isvg9jbyxe5xsmzz8vt.png)
b =
![(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e14yosw5rbprbu04e78upb04bghif5atho.png)
Therefore, equation of the exponential function will be,
g(x) =
![12.((3)/(4))^x](https://img.qammunity.org/2021/formulas/mathematics/high-school/x4vanzrdjfiwe02sfif21fet3g4wla0jeb.png)